The Impact of a Reduced High‐Wind Charnock Parameter on Wave Growth With Application to the North Sea, the Norwegian Sea, and the Arctic Ocean. Issue 3 (22nd March 2022) - Breivik, Øyvind; Carrasco, Ana; Haakenstad, Hilde; Aarnes, Ole Johan; Behrens, Arno; Bidlot, Jean‐Raymond; Björkqvist, Jan‐Victor; Bohlinger, Patrik; Furevik, Birgitte R.; Staneva, Joanna; Reistad, Magnar
Abstract: As atmospheric models move to higher resolution and resolve smaller scales, the maximum modeled wind speed also tends to increase. Wave models tuned to coarser wind fields tend to overestimate the wave growth under strong winds. A recently developed semiempirical parameterization of the Charnock parameter, which controls the roughness length over surface waves, substantially reduces the aerodynamic drag of waves in high winds (above a threshold of 30 m s −1 ). Here, we apply the formulation in a recent version of the wave model WAM (Cycle 4.7), which uses a modified version of the physics parameterizations by Ardhuin et al. (2010, https://doi.org/10.1175/2010jpo4324.1 ) as well as subgrid obstructions for better performance around complex topography. The new Charnock formulation is tested with wind forcing from NORA3, a recently completed nonhydrostatic atmospheric downscaling of the global reanalysis ERA5 for the North Sea, the Norwegian Sea and the Barents Sea. Such high‐resolution atmospheric model integrations tend to have stronger (and more realistic) upper‐percentile winds than what is typically found in coarser atmospheric models. A 2‐year comparison (2011–2012) of a control run against the run with the modified Charnock parameter shows a dramatic reduction of the wave height bias in high‐wind cases. The added computational cost of the new physics and the reduction of the Charnock parameter compared to the earlier WAM physics is modest (14%). A longer (1998–2020) hindcast integration with the new Charnock parameter is found to compare well against in situ and altimeter wave measurements both for intermediate and high sea states. Plain Language Summary: Wave models are sensitive to strong winds, and as the atmospheric models have increased in resolution, the strength of the winds has also increased as small‐scale features of synoptic storms become more realistically modeled. Here, we investigate the behavior of a bespoke version of the wave model WAM, where we have modified how waves grow in strong winds. More specifically, we have modified the so‐called Charnock parameter, which determines how rough the sea surface gets as the wind picks up. By making the sea surface smoother under strong winds, we reduce the growth of the waves under hurricane conditions in a manner which appears to be in line with recent studies of the behavior of the sea surface in very strong winds. The results match our observations very well over a wide range of conditions throughout the model domain and show a clear improvement over a control experiment with the same wave model without a modified Charnock parameter. Finally, a detailed wave hindcast, or sea state archive, for the Norwegian Sea, North Sea and the Arctic Ocean covering the period 1998–2020 is presented where this modified Charnock parameter is employed. The results compare well against observations. Key Points: A semiempirical parameterization for high‐wind drag (above 30 m s −1 ) is implemented in WAM A 2‐year comparison against a control run shows significant bias reduction in strong winds A 23‐year wave hindcast shows very good performance compared to satellite and buoy measurements